Gamma-spectroscopic analysis of NORM samples - Lazaraki, Despoina; Kalamara, Antigoni; Savva, Marilia I.; Vasilopoulou, Theodora (HNPS Advances in Nuclear Physics, 2024)
Two samples of Naturally Occurring Radioactive Materials (NORM) were studied using gamma-spectrometry in order to determine their radioactivity levels. The samples consisted of phosphate ore and phosphogypsum, a by-product of the phosphate fertilizer industry. Customized containers of standard geometry were filled with the above materials and then sealed with epoxy resin in order to prevent gaseous isotopes from emanating. The samples were measured by means of gamma spectrometry using a High-Purity Germanium detector. The full energy peak efficiency calibration of the detector was performed experimentally, using reference volume sources of the same geometry and density as those of the samples. To account for the true coincidence summing effect and the self-attenuation of gamma-rays within the samples volume, appropriate correction factors were calculated using the TrueCoinc software and the MCNP code, respectively. In both samples, 228Ac, 214Bi, 235U, 214Pb, 212Pb, 234Th, 208Tl and 40K were detected, with activity levels varying per isotope. The results of the present study provide information on the activity levels of NORM, which is important for Occupational Radiological Exposure assessments of workers in industries involving NORM, such as the phosphate fertilizer industry, as well as for the protection of the environment.